Applying e-commerce by Vietnamese SMEs: A critical analysis - Binh, Dang Thai; Hoa, Ho Thi; Hieu, Pham Van; Can, Bui Van; Hung, Do Hai; Dai, Nguyen Huu Phuoc (Journal of Social Economics Research, 2023)
Small and medium-sized enterprises (SMEs) play a crucial role in many countries’ economic growth and development, particularly in Vietnam. Vietnamese SMEs have been instrumental in creating job opportunities, especially for low-skilled laborers, and are increasingly contributing to the stability and progress of the national economy. However, the rise of globalization and the integration of economies at the international and regional levels have exposed SMEs to severe local and global competition. To sustain and develop their essential role in the face of rising competition, SMEs must innovate and adopt new technologies, with e-commerce being one of the essential solutions. The integration of e-commerce within Vietnamese Small and medium-sized enterprises (SMEs) has posed a significant challenge, making it crucial to identify the key factors that impact its implementation. A quantitative method was used to determine the four factors (Technology, Organizational, Environmental, and Management) influencing the adoption of e-commerce by Vietnamese SMEs. The study found that technology has the most significant impact on the adoption of e-commerce by Vietnamese SMEs, followed by organizational, management, and environmental factors. Technology is considered the most critical factor because e-commerce is primarily a technological solution, and SMEs need to invest in advanced technologies to keep up with their competitors.